Analysis of trends in implant therapy at a surgical specialty clinic: Patient pool, indications, surgical procedures, and rate of early failures—A 15‐year retrospective analysis. Issue 11 (30th August 2019) - Ducommun, Julien; El Kholy, Karim; Rahman, Lira; Schimmel, Martin; Chappuis, Viviane; Buser, Daniel
Abstract: Objectives: To evaluate the patient population over a 3‐year period and to compare it to observations of the population at the same clinic over a period of 15 years. Material and Methods: Records of patients receiving dental implants in the Department of Oral Surgery and Stomatology, University of Bern, between January 2014 and December 2016 were analyzed and then compared with data from patients treated between 2002 and 2004 and between 2008 and 2010. Patients were analyzed for demographics and for indications for therapy, as well as for presence or absence and type of complications. Inserted implants were analyzed for type, length, and diameter, as well as for the number and type of associated tissue regeneration procedures. Results: Analysis revealed a continuous linear increase in the average age of patients seeking implant treatment. The most common indication for implant therapy was a single‐tooth gap (STG) (50.5%), followed by distal extension situations (22.3%) and extended edentulous gaps (20.5%). A total of 60.8% of implants placed needed some type of bone augmentation, and 83.5% of implants placed in the anterior maxilla required simultaneous augmentation. Staged guided bone regeneration (GBR) was only necessary in 7% of the cases. Implant failure rates remained low at 0.6%, with postoperative hematomas being the most common postoperative complication (13.4%). Conclusions: The rising demand for dental implants continues as the patient population ages. Single‐tooth gaps remained consistently the most common indication for implant therapy in recent years. Proper case selection and evidence‐based surgical protocols are essential for high success rates.